Beijing's strategic encirclement of Australia - Matthews, Ron (Australian Public Affairs Information Service, 2021)
No country has come close to China's long-term growth rate, which has averaged a remarkable 9.5% over the last 40 years. This sustained high level of economic activity has enabled a parallel expansion in defence spending. While NATO countries are struggling to hit 2% growth targets, China's defence budget increased by 7% in 2021.
Keywords: Naval battles; Cyberspace operations (Military science); Military bases--Economic aspects; Infrastructure (Economics); Warships--Visits to foreign ports; Runways (Aeronautics)